PERANAN PESTISIDA BOTANI DALAM MENDUKUNG PERTANIAN ORGANIK - Sudiarta, I Putu (AGRICA, 2010)
Until recently the use of synthetic pesticides to control pest and plant diseases proved effective, but on the other hand, the excessive use of synthetic pesticides cause many negative effects, such as the development of pest and disease resistance, second pest explosion, death of natural enemies and pesticide residues in food and environment. One alternative that can be done to solve this problem is the use of botanical pesticides. Botanical pesticides are compounds produced as a plant defence response to disturbances and stimulation. These compounds generally are of secondary metabolites that have many functions, such as growth hormones (Auxin, gibberellins and cytokinins), anti-fungal or anti-bacterial, antibiotics, and toxic to animals and insects. The advantage of botanical pesticides is that they have toxicity similar to synthetic pesticides, but the botanical pesticides can be used to support sustainable organic agriculture.  Experiments in the utilization of botanical pesticides to control plant pest have been carried out. One example application is the use of botanical insecticides from ?Brotowali? leaf extract (Tinospora crispa) to control the diamond black caterpillars (Plutella xylostella)  on cabbage plants. In addition, the use of ?basil? oil (Ocimum tenuiflorum) has a real impact in population control of the fruit fly (Bactrocera dorsalis). In addition to pest control, botanical pesticides are also reported to effectively control plant diseases. Use of ?galangal? (Alpinia galanga) and papaya (Carica papaya) has a high ability to inhibit the growth of Ceratocystis sp. On PDA and fruits. The combination of ?betel? leaf extract (Piper betle) and ?galangal? (A galanga) can suppress the growth of banan wilt disease caused by Fusarium oxysporum and / or the Ralstonia solanacearum. The use of ?galangal? (A. Galanga) extract with a concentration of 5%, can also inhibit the growth of stem rot disease (F. oxisporum) on vanilla seedlings. In addition, the use of ?betel? ieaf P. Bettle in the field can suppress black rot disease on cocoa pods (cocoa black pd disease)